2021
DOI: 10.1155/2021/8643129
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Neuronal and Glial Two-Pore-Domain Potassium Channels in Health and Neurological Disorders

Abstract: Two-pore-domain potassium (K2P) channels are widespread in the nervous system and play a critical role in maintaining membrane potential in neurons and glia. They have been implicated in many stress-relevant neurological disorders, including pain, sleep disorder, epilepsy, ischemia, and depression. K2P channels give rise to leaky K+ currents, which stabilize cellular membrane potential and regulate cellular excitability. A range of natural and chemical effectors, including temperature, pressure, pH, phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…A previous study demonstrated the interaction between the two proteins sortilin and TREK-1, in which mice with deletions of the sortilin ( sort1 ) or TREK-1 ( kcnk2 ) genes displayed a similar phenotype of resistance to depressive-like behavior during resignation tests such as the forced swimming test (FST) and the tail suspension test (TST) [ 76 ]. TREK-1 belongs to the family of two-pore-domain potassium channels, which play important roles in neuroprotectioTablen, pain, analgesia, and depression [ 77 , 78 , 79 ]. As one of the first functions identified for Sortilin/NTSR3 was to address numerous proteins from the intracellular compartments to the plasma membrane or lysosomes [ 17 , 80 ], it was crucial to determine whether sortilin and TREK-1 were associated, and if they were, how sortilin was involved in the sorting of TREK-1.…”
Section: Another Crucial Function Of Sortilin/ntsr3: Possible Role In...mentioning
confidence: 99%
“…A previous study demonstrated the interaction between the two proteins sortilin and TREK-1, in which mice with deletions of the sortilin ( sort1 ) or TREK-1 ( kcnk2 ) genes displayed a similar phenotype of resistance to depressive-like behavior during resignation tests such as the forced swimming test (FST) and the tail suspension test (TST) [ 76 ]. TREK-1 belongs to the family of two-pore-domain potassium channels, which play important roles in neuroprotectioTablen, pain, analgesia, and depression [ 77 , 78 , 79 ]. As one of the first functions identified for Sortilin/NTSR3 was to address numerous proteins from the intracellular compartments to the plasma membrane or lysosomes [ 17 , 80 ], it was crucial to determine whether sortilin and TREK-1 were associated, and if they were, how sortilin was involved in the sorting of TREK-1.…”
Section: Another Crucial Function Of Sortilin/ntsr3: Possible Role In...mentioning
confidence: 99%
“…Depolarisation of the resting membrane potential and neuronal hyperexcitability are consistent with previously reported data in numerous tauopathy models [ 61 , 108 , 122 , 132 ], for example in the rTg4510 mouse model, which expresses human tau variant P301L, where the pyramidal cells were depolarised by ∌8 mV compared to WT littermates [ 108 ]. The increase in input resistance and firing rate, coupled with the observed depolarisation could result from the block of a standing (or leakage) conductance for example a two-pore-domain potassium (K2P) channels that contribute to maintaining the resting potential [ 87 ]. A comparable increase in neuronal hyperexcitability has also been observed in AD patients in individuals performing memory-encoding tasks [ 28 , 41 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depolarisation of the resting membrane potential and neuronal hyperexcitability are consistent with previously reported data in numerous tauopathy models [59, 105, 118, 128], for example in the rTg4510 mouse model, which expresses human tau variant P301L, where the pyramidal cells were depolarised by ~8 mV compared to WT littermates [105]. The increase in input resistance and firing rate, coupled with the observed depolarisation could result from the block of a standing (or leakage) conductance for example a two-pore-domain potassium (K2P) channels that contribute to maintaining the resting potential [84].…”
Section: Discussionmentioning
confidence: 99%